IMPLEMENTASI ENTERPRISE RESOURCE PLANNING (ERP) BERBASIS ODOO MODUL RENTAL & WEBSITE E-COMMERCE PADA PRASETYA OUTDOOR - Halim, Haneda; Veronika, Helena; Kamaliyah, Sarifatul; Firzanah , Nur Amalina; Rochmadi, Tri; Ratnasari, Asti; Harahap, Avrillaila Akbar; Pramuntadi , Andri (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The development of information technology today, a business can be integrated into all business activities from sales to customer relations into one system. Thus, all employees in various divisions of the company can report their activities in the system. The need for efforts to optimize the role of their information technology to run effectively and optimally. Prasetya Outdoor realizes the importance of maintaining service quality and optimizing business processes. Prasetya Outdoor intends to improve its competitiveness by adopting an Odoo-based ERP system with a focus on the rental module and website. Here are some of the methods used by the camping equipment rental at Prasetya outdoor: Online Booking, Physical On-site Rental, Rental Packages, and Customer Service. The obstacles that occur in the Prasetya Outdoor rental business are problems regarding marketing development and inventory management that are still not maximized. So the conclusion is that the entire system created can meet the needs of Prasetya Outdoor partners in terms of marketing and inventory management because the implementation of Odoo ERP in the Prasetya Outdoor rental business includes a rental module and an e-commerce website module. Hopefully in the future, the rental module and e-commerce website can be further expanded and optimized.